2018
DOI: 10.1002/jcp.26946
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous hydrogen sulfide attenuates the development of diabetic cardiomyopathy via the FoxO1 pathway

Abstract: Our data indicate that H S is a novel regulator of FoxO1 in cardiac cells and provide evidence supporting the potential of H S in inhibiting the progression of DCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…In the present study, the inhibition of the STAT3/HIF-1α pathway reduced ROS generation, MDA content and NOX2 expression, and increased SOD activity and GSH level, attenuating oxidative stress and promoting the antioxidant defense system. On the other hand, previous studies have suggested that exogenous H 2 S alleviates the development of DCM by inhibiting oxidative stress (52,53). Consistent with these observations, the present study also revealed that GYY4137 pretreatment eliminates HG-induced oxidative stress, which was a similar effect to that of inhibition of the STAT3/HIF-1α pathway.…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, the inhibition of the STAT3/HIF-1α pathway reduced ROS generation, MDA content and NOX2 expression, and increased SOD activity and GSH level, attenuating oxidative stress and promoting the antioxidant defense system. On the other hand, previous studies have suggested that exogenous H 2 S alleviates the development of DCM by inhibiting oxidative stress (52,53). Consistent with these observations, the present study also revealed that GYY4137 pretreatment eliminates HG-induced oxidative stress, which was a similar effect to that of inhibition of the STAT3/HIF-1α pathway.…”
Section: Discussionmentioning
confidence: 95%
“…FOXO1 is also known as forkhead within the rhabdomyosarcoma, as well as a transcription factor playing an important role in regulation of gluconeogenesis 28, 29. In VSMCs, FOXO1 has been powerfully proven to regulate vascular remodeling and diabetic cardiomyopathy 30, 31. In addition, FOXO1 functions a transcription factor to modulate the human cancers 32 .…”
Section: Discussionmentioning
confidence: 99%
“…In turn, Ca 2+ /CaM can regulate the activity of CSE and the formation of H 2 S [102]. Exogenous H 2 S improves cardiac function and attenuates cardiac hypertrophy and myocardial fibrosis in diabetic mice via the forkhead box protein O1 (FOXO1) pathway [112]. This protein plays important roles in the regulation of gluconeogenesis and glycogenolysis by insulin signaling; hence, by increasing exogenous H 2 S, protective effects against diabetic cardiomyopathy are attained.…”
Section: Diarylheptanoidmentioning
confidence: 99%